From Equal Rights to Far-Right: A study of the role of women in the political and social legitimization of far-right movements. - Chiquette, Sophie (Université d'Ottawa | University of Ottawa, 2022)
During the last 10 years there has been a disturbing global political trend. Indeed, far-right movements have been on the rise in both Europe and the United States, and they have already had documented effects on the decline of Western liberal democracies. Their draconian views on race and gender, along with their penchant for authoritarianism are driving factors in a need to better understand how these movements rise in popularity despite their polarizing and extreme views. While there exists a vast collection of literature on the topic, one element remains under studied and will be the subject of this paper. The question of gender remains a guiding principle in the ideology of the far-right. However, those who study these movements often disregard the role women play in the popularization of these political parties. This paper seeks to close that gap by outlining what role women play in the social and political legitimization of far-right movements. This is illustrated using two case studies: The Jobbik party in Hungary and the Republican Party in the United States. Despite the existing gender gap among the supporters of the far-right, the number of female supporters continues to rise. Women are clearly seeing a benefit to adhering to and participating in this ideology. Understanding this phenomenon is essential to understanding the movements and ways to counter them.